Invasive fungal infections in acute myeloid leukemia treated with venetoclax and hypomethylating agents - Aldoss, Ibrahim (Blood Adv, 2019)
The combination of venetoclax with hypomethylating agents (VEN-HMAs) showed promising activity in newly diagnosed and relapsed/refractory (r/r) acute myeloid leukemia (AML). Treatment with VEN-HMAs results in prolonged cytopenia, thereby exposing patients to invasive fungal infections (IFIs). Here, we retrospectively studied a cohort of 119 AML patients treated with VEN-HMAs and analyzed the occurrence of IFIs, as well as our practice of antifungal prophylaxis, with the aim to identify the nature and risk factors for IFIs and their association with the type of antifungal prophylaxis used. The intended antifungal prophylaxis was micafungin in 38% of patients, azoles in 41% of patients, and none in 21% of patients. Older age was associated with no antifungal prophylaxis or micafungin use and lesser use of azoles (P = .043). We recorded 15 (12.6%) patients who developed probable or proven IFIs, with a median onset of 72 days (range, 35-281) after starting therapy. IFIs were more common among nonresponders compared with responders to VEN-HMA therapy (22% vs 6%, P = .0132) and in r/r compared with newly diagnosed AML (19% vs 5%, P = .0498); however, the antifungal prophylaxis used, patient age, hypomethylating agent schedule, history of prior allogeneic transplant, and initial neutropenia duration did not influence the development of IFIs during therapy. We conclude that the overall risk of IFIs during VEN-HMA therapy is low. The risk of IFIs is higher in nonresponders and in those who were treated in the r/r setting; these patients need reevaluation of their antifungal prophylaxis to minimize the risk of IFIs during therapy.